Future Problem-Solving Practiced During COVID-19: Implications for Health Management Students' E-Health Literacy Identity - Alt, Dorit; Naamati-Schneider, Lior; Meirovich, Adaya (Frontiers in Psychology, 2022)
The current study describes the implementation of an online Future Problem Solving (FPS) program in the field of Health education and set out to explore its contribution to students’ eHealth Literacy identity, by using two levels of teacher guidance: minimal vs. frequent. FPS was employed in two groups of Health students. In the research group, frequent weekly guidance was provided to the students centered on the enhancement of eHealth Literacy skills, whereas in the control group minimal guidance was offered by the lecturer. Data for the analysis were gathered from 113 Israeli undergraduate students of a Management of Health Service Organizations program, of whom 62 comprised the research group. Data were gathered twice, pre- and post-program implementation from both groups. Findings showed significant differences between the tests only for the research group, with increased levels of eHealth Literacy skills detected between the tests. The perception of the FPS program as meaningful contributed to students’ perceived eHealth Literacy skills only in the research group whereas non-significant results were shown for the control group. This study mainly shows that the enhancement of skills in online educational environments requires frequent and personalized guidance. Faculty must recognize the role of the instructor as a facilitator of learning and design successful scaffolding strategies to nurture students’ lifelong learning skills during distance learning.